ChemInform Abstract: Direct Nucleophilic Substitution of Free Allylic Alcohols in Water Catalyzed by FeCl3·6H2O: Which Is the Real Catalyst?. Issue 46 (24th October 2013) - Trillo, Paz; Baeza, Alejandro; Najera, Carmen
Abstract The reaction is environmentally friendly and is applied to various N‐, C‐ and O‐nucleophiles.